2009
DOI: 10.1504/ijbaaf.2009.022716
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the suspension of opening and closing call auctions: evidence from the National Stock Exchange of India

Abstract: We study the impact of the suspension of opening and closing call auctions by the National Stock Exchange of India in 1999. We compare volatility, efficiency and liquidity (VEL) of securities before and after suspension, and estimate the value of the auctions using an event study. Following suspension, VEL improved and the CARs were significant but not uniformly positive or negative. Also, less liquid stocks traded less in the auctions than other securities, especially at the opening, and they experienced gain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 42 publications
3
10
0
Order By: Relevance
“…These findings challenge the intuition that by aggregating the orders of a cross-section of traders, call auctions enhance price discovery and reduce the dispersion of prices around fundamental values. The above evidence is in line with that of Camilleri and Green (2009) and Camilleri (2015) that the NSE call auctions were less effective than one may expect. Despite this, the results of this paper differ from prior studies outlined above which associated the presence of call auctions with reduced volatility (Comerton-Forde, 1999;Chang et.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…These findings challenge the intuition that by aggregating the orders of a cross-section of traders, call auctions enhance price discovery and reduce the dispersion of prices around fundamental values. The above evidence is in line with that of Camilleri and Green (2009) and Camilleri (2015) that the NSE call auctions were less effective than one may expect. Despite this, the results of this paper differ from prior studies outlined above which associated the presence of call auctions with reduced volatility (Comerton-Forde, 1999;Chang et.…”
Section: Resultssupporting
confidence: 88%
“…For instance, Camilleri and Green (2009) reported that only 7% to 18.6% of the less liquid stocks in their sample traded in the NSE opening auction. Nonetheless, given that in this paper we use index data which are computed through a portfolio of highly liquid stocks, such factors might not have any direct impacts on our findings.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations